SIRT6 Acts as a Negative Regulator in Dengue Virus-Induced Inflammatory Response by Targeting the DNA Binding Domain of NF-κB p65 - Li, Pengcheng; Jin, Yufei; Qi, Fei; Wu, Fangyi; Luo, Susu; Cheng, Yuanjiu; Montgomery, Ruth R.; Qian, Feng (Frontiers in Cellular and Infection Microbiology, 2018)
Dengue virus (DENV) is a mosquito-borne single-stranded RNA virus causing human disease with variable severity. The production of massive inflammatory cytokines in dengue patients has been associated with dengue disease severity. However, the regulation of these inflammatory responses remains unclear. In this study, we report that SIRT6 is a negative regulator of innate immune responses during DENV infection. Silencing of Sirt6 enhances DENV-induced proinflammatory cytokine and chemokine production. Overexpression of SIRT6 inhibits RIG-I-like receptor (RLR) and Toll-like receptor 3 (TLR3) mediated NF-κB activation. The sirtuin core domain of SIRT6 is required for the inhibition of NF-κB p65 function. SIRT6 interacts with the DNA binding domain of p65 and competes with p65 to occupy the Il6 promoter during DENV infection. Collectively, our study demonstrates that SIRT6 negatively regulates DENV-induced inflammatory response via RLR and TLR3 signaling pathways.